2019
DOI: 10.18203/2349-2902.isj20194439
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of quality of life in patients with enterostomy

Abstract: Background: Enterostomy is one of the commonest surgeries performed in general surgical practise. It leads to considerable alteration in life style of patients after surgery in the form of physical, mental, social, spiritual, economic, educational, vocational, marital, sexual problems. We designed study to assess the extent of these affections on quality of life (QOL) and suggest measure to improve it.Methods: We conducted a cross sectional survey using validated City of Hope-quality of life-Ostomy questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
(8 reference statements)
3
3
0
Order By: Relevance
“…Our results also showed that nearly two-thirds of respondents identified as being sexually active prior to their ostomy formation, with only approximately one-quarter reporting postsurgical sexual activity. This is consistent with findings of past studies reporting that the presence of a stoma adversely affected one’s ability to engage in intimacy, negatively affecting overall QoL (Anaraki et al, 2012; Dhamnaskar et al, 2019; Gemmill et al, 2010). Lower overall and gender-specific proportions of poststoma sexual activity were reported in an Iranian study (Anaraki et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results also showed that nearly two-thirds of respondents identified as being sexually active prior to their ostomy formation, with only approximately one-quarter reporting postsurgical sexual activity. This is consistent with findings of past studies reporting that the presence of a stoma adversely affected one’s ability to engage in intimacy, negatively affecting overall QoL (Anaraki et al, 2012; Dhamnaskar et al, 2019; Gemmill et al, 2010). Lower overall and gender-specific proportions of poststoma sexual activity were reported in an Iranian study (Anaraki et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…The overall level of QoL reported by this sample of people living with a stoma in nonmetropolitan Australia was moderate to high. This result is comparable to the levels of stoma-related QoL reported in studies conducted internationally ( Anaraki et al, 2012 ; Cotrim & Pereira, 2008 ; Dhamnaskar et al, 2019 ; Konjevoda et al, 2020 ; Yilmaz et al, 2017 ). Two studies that also used the QOL-O reported similar findings for the overall QoL score ( Anaraki et al, 2012 ; Konjevoda et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations